2012
DOI: 10.2174/187152512799201172
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Aspect of Beta-Thalassaemia

Abstract: Beta-thalassaemia major is a genetic blood disorder caused by the reduced synthesis of beta globin chain. The consequences of the resulting chronic anaemia are also common and include growth retardation, bone marrow expansion, extramedular hematopoiesis, splenomegaly, increased intestinal iron absorption, susceptibility to infections, and hypercoagulability. Transfusional iron overload can affect heart function by directly damaging tissue through iron deposition or via iron-mediated effects at other sites. Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…This hereditary disorder of metabolism can lead to organ damage and mortality [31,32], if left undiagnosed and untreated. Iron deposition in the parenchymal tissues of thalassemia patients can be observed within a year of the onset of regular blood transfusions [33]. Studies have shown that iron gets accumulated in the cardiac, endocrine, hepatic tissues and gingivae of thalassemia major patients [34,35].…”
Section: Dental Infectionsmentioning
confidence: 99%
“…This hereditary disorder of metabolism can lead to organ damage and mortality [31,32], if left undiagnosed and untreated. Iron deposition in the parenchymal tissues of thalassemia patients can be observed within a year of the onset of regular blood transfusions [33]. Studies have shown that iron gets accumulated in the cardiac, endocrine, hepatic tissues and gingivae of thalassemia major patients [34,35].…”
Section: Dental Infectionsmentioning
confidence: 99%
“…18 Peningkatan EF juga dianggap sebagai tahap awal kardiomiopati, yaitu peningkatan EF >60% atau terdapat hipertensi arteri pulmonal ringan (HAP), regurgitasi mitral (MR), atau trikuspid (TR). 19 Gangguan fungsi diastol pada penyandang TM berbentuk gangguan restriktif, yaitu nilai E/A >1,5 dengan nilai DT <150 m/s 20 maka subjek penelitian kami terpenuhi pada 21 pasien, walaupun tidak berkorelasi dengan penurunan kadar ion kalsium. Hal tersebut mungkin disebabkan adanya mekanisme kompensasi pada anemia kronik yang mempertahankan fungsi diastol normal.…”
Section: Hasilunclassified
“…Certain communities in India, like Sindhis, Gujratis, Punjabis, and Bengalis, are more commonly affected with beta thalassemia, the incidence varying from 1 to 17% [3] Iron overload which is a common complication of thalassaemic syndromes could lead per se to the development of organ damage and increased mortality [4]. In these patients, iron deposition in parenchymal tissues starts within 1 year of starting the regular transfusions [5]. Blood transfusions are important for survival of these patients, but chronic transfusions inevitably lead to iron overload as humans cannot remove excess iron actively.…”
Section: Introductionmentioning
confidence: 99%